The Typological Features of Lexicalization - Grdzelyan, Rouzan (Bulletin of Yerevan University H: Russian Philology, 2022)
The study of ways and methods of lexicalization in the Russian and Armenian languages contributes to a more detailed description of the lexical and typological characteristics of these languages. The article is devoted to the description of one of the ways of lexicalization – word composition. Despite the fact that this word-formation model is peculiar to both the Russian and Armenian languages, its use has its own characteristics – different frequency of use, different semantic structure, different ratio between the composite and the simple word synonymous with it, the composite and the phrase, different motivation for choosing a particular unit. The article outlines the directions in which further research should be conducted.
Keywords: lexicalization; verbalization; compounding; lexoid; typology